1993
DOI: 10.1111/j.1467-9906.1993.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Characteristics and Redistribution Efforts: Oklahoma’S Participation in the Cdbg Small Cities Program

Abstract: Decentralization of the CDBG Small Cities program caused a shift in spending priorities among grant recipients. This paper attempts to identify the variables influencing urban policy choices with respect to the CDBG Small Cities program in Oklahoma. Findings suggest that redistributive effort is heightened by greater citizen awareness of the program and low income participation. However, in the majority of grant communities, residents are not extensively involved in CDBG decisionmaking, relying instead on loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This finding makes sense in light of our framework because both pre‐1981 HUD and post‐1981 state administration use some form of competitive grant contracting. Isserman (1981) found that need was generally ignored in HUD’s administration, and Watson’s (1992, 1993) studies of Oklahoma suggest that state administration may be targeting median income populations to the exclusion of poor communities. These findings are consistent with the proposition that reliance on grant competitions may bias outputs toward greater administrative capacity.…”
Section: Social Equity In State‐administered Cdbg Programsmentioning
confidence: 99%
“…This finding makes sense in light of our framework because both pre‐1981 HUD and post‐1981 state administration use some form of competitive grant contracting. Isserman (1981) found that need was generally ignored in HUD’s administration, and Watson’s (1992, 1993) studies of Oklahoma suggest that state administration may be targeting median income populations to the exclusion of poor communities. These findings are consistent with the proposition that reliance on grant competitions may bias outputs toward greater administrative capacity.…”
Section: Social Equity In State‐administered Cdbg Programsmentioning
confidence: 99%